Survey on robust control of precision positioning systems - Raafat, Safanah M.; Akmeliawati, Rini (2012)
A very high accuracy and resolution, stability, and fast response are the requirements of high precision positioning systems (HPPS). Accurate position sensing and feedback control of the motion are key to the successful precision positioning. In this paper, the robust control of HPPS literature published within last two decades is categorized and discussed. The paper also provides detailed technical descriptions on many such novel methods. According to the type of the control methodology applied in the reviewed literature, the paper categorizes them into seven main categories. The purpose is to emphasize the key role of advanced control techniques in improving precision, accuracy, and the speed of operation of these systems. While doing so, the paper also reviews literature on various applications of robust control for HPPS including some recent patents. However, the list of patents reviewed is not the least assumed to be complete or general. Nevertheless, the evolution and trends in the applications of robust control methods are shown. Based on the analysis of the reviewed patents, the expected future developments in this domain are highlighted.